Sosialisasi Olahraga Bela Diri Shorinji Kempo Pada Siswa MTS Al - Falah Fi’lial Pulubala Kabupaten Goronntalo - Zulkifli Lamusu; Risna Podungge (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the martial arts sports currently showing rapid development is Shorinji Kempo. In an effort to find potential athletes, it is necessary to provide outreach to the younger generation, among the younger generation the most appropriate are students who are in junior high school or equivalent, because on average they are very happy with martial arts sports. There is a need for shorinji kempo self-defense training at MTs. As a first step in introducing shorinji kempo self-defense at MTs Al-Falah, it is necessary to provide socialization about the basic techniques of self-defense in this area. From this socialization activity, it is hoped that it will attract the interest of MTs Al-Falah Pulubala students to take part in further training so that with the training that will be followed later, the seeds of Shorinji Kempo martial arts athletes will be created who in the future can make the name of the school and the name of the region and even our beloved country, Indonesia. . From the entire series of socialization activities for students at MTs AL-Falah Fi'lial Pulubala this gave quite good results, on average most of the students understood theoretically the history and philosophy of Shorinji Kempo martial arts and the most important thing was that most of the participants could perform a series of basic Shorinji technique movements.